2013
DOI: 10.1590/1414-431x20132483
|View full text |Cite
|
Sign up to set email alerts
|

Chromogenic in situ hybridization compared with other approaches to evaluate HER2/neu status in breast carcinomas

Abstract: Human epidermal growth factor receptor 2 (HER2) has been evaluated in breast cancer patients to identify those most likely to benefit from herceptin-targeted therapy. HER2 amplification, detected in 20-30% of invasive breast tumors, is associated with reduced survival and metastasis. The most frequently used technique for evaluating HER2 protein status as a routine procedure is immunohistochemistry (IHC). HER2 copy number alterations have also been evaluated by fluorescence in situ hybridization (FISH) in mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 73 publications
(114 reference statements)
1
22
0
Order By: Relevance
“…Owing to its resemblance to immunohistochemistry staining (57), CISH is also easier to interpret by pathologists who are not trained in fluorescence microscopy. Furthermore, in previous studies, CISH was observed to be well-correlated with FISH (46,(58)(59)(60). The present study used standard CISH to demonstrate that HER2 was amplified in Iranian (Tehran province) patients with PCa.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Owing to its resemblance to immunohistochemistry staining (57), CISH is also easier to interpret by pathologists who are not trained in fluorescence microscopy. Furthermore, in previous studies, CISH was observed to be well-correlated with FISH (46,(58)(59)(60). The present study used standard CISH to demonstrate that HER2 was amplified in Iranian (Tehran province) patients with PCa.…”
mentioning
confidence: 66%
“…Permanent staining and the absence of a fluorescent dye make CISH a suitable replacement for FISH (69). In addition, its usability, relative inexpensiveness and speed make CISH more attractive than FISH for assessing HER2 amplification/overexpression (59,70).…”
mentioning
confidence: 99%
“…First, IHC scores vary depending on the antibodies used [9]. Second, IHC is sensitive to pre-analytical variation, including tissue fixation [31].…”
Section: Discussionmentioning
confidence: 99%
“…These two techniques, demonstrating excellent concordance [9], are less sensitive to pre-analytical variation than IHC, but they are labor-intensive, expensive and somewhat difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are used worldwide to test for HER2 overexpression/amplification within routine pathology. However, HER2 IHC analysis is influenced by several factors including fixation time, antigen retrieval and antibody specificity and sensitivity (6,(19)(20)(21)(22). Furthermore, the interpretation of HER2 IHC is semi-quantitative and subjective, which may lead to inter-observer variability affecting the accuracy of the results (23)(24)(25).…”
mentioning
confidence: 99%